Segmental sandwich osteotomy and tunnel technique for three-dimensional reconstruction of the jaw atrophy: a case report - Mario Santagata; Nicola Sgaramella; Ivo Ferrieri; Giovanni Corvo; Gianpaolo Tartaro; Salvatore D'Amato (SpringerOpen, 2017)
Abstract Background A three-dimensionally favourable mandibular bone crest is desirable to be able to successfully implant placement to meet the aesthetic and functional criteria in the implant-prosthetic rehabilitation. Several surgical procedures have been advocated for bone augmentation of the atrophic mandible, and the sandwich osteotomy is one of these techniques. The aim of the present case report was to assess the suitability of segmental mandibular sandwich osteotomy combined with a tunnel technique of soft tissue. Based on our knowledge, nobody described before the sandwich osteotomy with tunnel technique to improve the healing of the wound and meet the dimensional requirements of preimplant bone augmentation in cases of a severely atrophic mandible. Case presentation A 59-year-old woman with a severely atrophied right mandible was treated with the sandwich osteotomy technique filled with autologous bone graft harvested by a cortical bone collector from the ramus. Clinical examination revealed that the mandible was edentulous bilaterally from the first molar to the second molar region. Radiographically, atrophy of the mandibular alveolar ridge in the same teeth site was observed. We began to treat the right side. A horizontal osteotomy of the edentulous mandibular bone was then made with a piezoelectric device after tunnel technique of the soft tissue. The segmental mandibular sandwich osteotomy (SMSO) was finished by two (mesial and distal) slightly divergent vertical osteotomies. The entire bone fragment was displaced cranially, and the desirable position was obtained. The gap was filled completely with autologous bone chips harvested from the mandibular ramus through a cortical bone collector. No barrier membranes were used to protect the grafts. The vertical incisions were closing with interruptive suturing of the flaps with a resorbable material. In this way, the suture will not fall on the osteotomy line of the jaw; the result will be a better predictability of soft and hard tissue healing. Conclusions Segmental mandibular sandwich osteotomy is an easy and safety technique that could be performed in an atrophic posterior mandible. Future studies involving long-term follow-up are needed to evaluate the permanence of these results.